Electoral competition and democratic decline in Nicaragua: uncovering an electorally viable platform for the right. Issue 6 (19th September 2017) - Anderson, Leslie E.; Dodd, Lawrence C.; Park, Won-ho
ABSTRACT: Between the 1980s and 2006 Nicaragua was a competitive democracy where parties of the left and right won national presidential elections and relinquished power when their terms ended. More recently the quality of Nicaragua's democracy has deteriorated. This change is due partly to autocratic behaviour by the elected leftist president, Daniel Ortega. But democratic decline is also the result of factional divisions and vague, outmoded policy commitments on the right that have crippled its electoral competitiveness, enabling Ortega's behaviour. Utilizing an experimental research design, this article identifies two modernized policy platforms that could significantly broaden rightist electoral support in presidential campaigns, aiding democratic resurgence in Nicaragua. At a point when opposition parties are struggling to retain strength and coherence in many other democracies, the study presents a research strategy that could help clarify the ways such parties might reinvigorate their electoral competitiveness.